Evaluation of an onco-diet on body composition and inflammatory status of dogs with mammary tumor-Pilot study. - Brana S A Bonder; Fabio A Teixeira; Mariana Y H Porsani; Lucas A Gonçales; Julio K Nagashima; Clair M de-Oliveira; Julio C C Balieiro; Karina Pfrimer; Cristina de O Massoco; Denise T Fantoni; Cristiana F F Pontieri; Marcio Antonio Brunetto (PLoS ONE, 2023)
A high-protein hypercaloric diet enriched with glutamine and omega-3 polyunsaturated fatty acids was called an onco-diet. The goal was to verify the modulation of the inflammatory response and body composition of female dogs with mammary tumor after mastectomy, during onco-diet consumption, using a randomized, double-blinded, clinical trial. Six bitches (average age of 8.6 years) were allocated into Control Group-diet without glutamine, EPA and DHA supplementation; and six bitches (10.0 years) were allocated into Test-diet enriched with glutamine and omega-3. Serum measurements of TNF-α, IL-6, IL-10, IGF-1, C-reactive protein and determination of body composition were performed at pre- and post-surgical times. Statistical tests were used to compare the nutrient intake and dietary effects on inflammatory variables between the diets. No differences in concentrations of different cytokines (p>0.05) and C-reactive protein (CRP) (p = 0.51) were observed between the groups. The test group had a higher concentration of IGF-1 (p<0.05), higher percentage of muscle mass (p<0.01) and lower body fat (p<0.01), but the difference was present from initial and throughout the study. Onco-diet, enriched with glutamine and omega-3, in the amounts evaluated in this study, was not sufficient to modulate the inflammation and body composition of female dogs with mammary tumors submitted to unilateral mastectomy.